Resíduo líquido do processamento da mandioca (manipueira) na alimentação de suínos - Barbosa, Rosylaine de Jesus (2012)
Some of the major problems faced by pig farmers are the oscillations of supply of grains commonly used in animal feed, to reduce the impacts caused by the fluctuating prices, has used low cost alternative foods. Cassava (Manihot esculenta, Crantz) is important to humans as a source of carbohydrates and has excellent nutritional quality for animal feed, among its byproducts can cite Manipueira, however, become necessary feasibility studies on its use in the husbandry of swine in growing and finishing due to the presence of the toxic principle known as hydrocyanic acid. For this purpose, it is recommended to reduce the concentration of antinutritional factors and assess the availability of nutrients present in food for use in feed for pigs. In this context, this study aimed evaluate the use of liquid residue of the cassava in different inclusion levels in diets for pigs of average initial weight of 38 kg to slaughter, making the characterization of liquid residue of the cassava to be included diets and verifying the influence of inclusion on the performance, organ weights, pH of the stomach and economic feasibility of using this product.